3‐D high‐speed imaging of volcanic bomb trajectory in basaltic explosive eruptions. (20th October 2016) - Gaudin, D.; Taddeucci, J.; Houghton, B. F.; Orr, T. R.; Andronico, D.; Del Bello, E.; Kueppers, U.; Ricci, T.; Scarlato, P.
Abstract: Imaging, in general, and high speed imaging in particular are important emerging tools for the study of explosive volcanic eruptions. However, traditional 2‐D video observations cannot measure volcanic ejecta motion toward and away from the camera, strongly hindering our capability to fully determine crucial hazard‐related parameters such as explosion directionality and pyroclasts' absolute velocity. In this paper, we use up to three synchronized high‐speed cameras to reconstruct pyroclasts trajectories in three dimensions. Classical stereographic techniques are adapted to overcome the difficult observation conditions of active volcanic vents, including the large number of overlapping pyroclasts which may change shape in flight, variable lighting and clouding conditions, and lack of direct access to the target. In particular, we use a laser rangefinder to measure the geometry of the filming setup and manually track pyroclasts on the videos. This method reduces uncertainties to 10° in azimuth and dip angle of the pyroclasts, and down to 20% in the absolute velocity estimation. We demonstrate the potential of this approach by three examples: the development of an explosion at Stromboli, a bubble burst at Halema'uma'u lava lake, and an in‐flight collision between two bombs at Stromboli. Key Points: First stereographic use of high speed cameras to reconstruct trajectories of pyroclasts in 3‐D First‐order model allowing a 10° precision for azimuth and dip, and a 20% for velocities Applications include Strombolian explosions, bubble bursts in lava lakes and in‐flight collisions